Effects of the Trigonella foenum-graecum L. seed extract and chromium picolinate supplementation in streptozotocin induced diabetes in rats - Atila, Gozde; Yuce, Abdurrauf (Natl Inst Science Communication-Niscair, 2016)
Our objective was to determine the effects of the Trigonella foenum-graecum seed extract and chromium picolinate in streptozotocin (STZ) induced diabetes in rats. We used 60 female Sprague Dawley rats aged between 2-3 months, who were divided into 6 groups: control (C);vehicle received physiological saline solution intraperitoneally (i.p.) + physiological saline solution orally, diabetescontrol group (DC); 50 mg/kg STZ i.p. + physiological saline solution orally, T. foenum-graecum (TFG); 50 mg/kg STZ i.p + 150 mg/kg TFG seed extract orally, chromium picolinate (Crpic); 50 mg/kg STZ i.p + 30 mu g/kg Chromium picolinate orally, T. foenum-graecum + chromium picolinate (TFG+Crpic); 50 mg/kg STZ i.p. + received 150 mg/kg TFG + 30 mu g/kg Crpic orally, insulin (I); 50 mg/kg STZ i.p. + 1 IU insulin subcutaneously. The treatment lasted for 21 days. On the 14th and 21st days, we found a decrease in theFBG of animals treated with insulin, TFG, TFG + Crpic combined (all p < 0.001), and Crpic (p < 0.01) compared with the diabetes control group. Moreover, there was a significant decrease in the plasma triglyceride and very low density lipoprotein (VLDL) levels after a treatment with Crpic, I, TFG, and TFG+Crpic compared with diabetes control group (p < 0.001). Administration of TFG+Crpic caused a significant increase in plasma high density lipoprotein (HDL) levels (p < 0.05) compared with diabetes control group. There was a significant decrease in the plasma tumor necrosis factor alpha (TNF-alpha) level after a treatment with Crpic (p < 0.05). The TFG, TFG and Crpic combined, and insulin treatment significantly increased the insulin-positive beta cells compared with diabetes control group (p < 0.001). These results show that the TFG extract may have an insulinotropic effect on the beta cells of the islets of Langerhans, or may prevent the damage of the pancreatic 13 cells. Crpic did not stimulate insulin secretion from the beta cells in the Langerhans islets. We concluded that Crpic may exert its antihyperglycemic effects by facilitating the interaction between insulin and its receptor. It is recommended that the TFG seed extract and Crpic supplements may help in alleviating or reducing the hyperglycemia-related chronic complications of diabetes.
Keywords: Diabetes mellitus; Trigonella foenum-graecum; Chromium picolinate; Proinflammatory cytokines; Lipid profile